América Latina en una encrucijada: ¿Modernizaciones alternativas, postliberalismo o posdesarrollo? - Escobar, Arturo (Revista Controversia, 2011)
El artículo caracteriza las actuales transformaciones socioeconómicas, políticas y culturales en Sudamérica, se pregunta si estas constituyen formas alternativas de modernización o si tienden a transformaciones sociales más radicales que podrían definiré como “alternativas a la modernidad”. Discute los cambios específicos introduciendo en los estados de Ecuador y Bolivia y su relación con los movimientos sociales. Plantea un debate entre formas liberales y post-liberales en términos de ontologías dualistas y relacionales. Concluye contrastando las distintas perspectivas de los estados y los movimientos sociales ante las transformaciones en marcha. Latin America at a Crossroad: Alternative Modernization, Postliberalism or Postdevolepment? This article discusses the current socioeconomic, political, and cultural transformations in South America, it wonders if these are alternative forms of modernization or if these tend to be more redical social changes, which might be defined as “alternative modernity”. Discusses the specific changes introduced in the state of Ecuador and Bolivia, and its relationship to social movements. This article proposes also a debate between liberal and post-liberal forms in terms of dualist and relational ontology. It concludes by contrasting the different perspective of states and social movements in face off the changes in progress. Keywords: Modernities, Post-Development, Social Movements, Ecuador, Bolivia, Ontologies.